The Sleep-Athlete Paradox: Assessing Sleep Quality and Behavior Among Collegiate Athletes - Dr. Nikhil Roy M; Dr. Ashirwad Jadhav; Dr. Sneha T Sambandam; Prof.Dr. Dobson Dominic (International Journal of Medical Toxicology and Legal Medicine, 2024)
Poor sleep quality significantly impacts athletes’ cognitive, motor, and emotional functioning. Assessment methods vary from objective tools to simple subjective approaches like sleep diaries and questionnaires. A cross-sectional study involving 107 university athletes utilized self-administered questionnaires (ASSQ and ASBQ) to assess sleep quality and behavior, ensuring a 95% confidence interval. Only 34% reported satisfactory sleep quality, with notable correlations between sleep difficulties and poor sleep behavior, and environmental conditions strongly linked to sleep difficulty scores. Personalized sleep education and interventions are essential for collegiate athletes to improve sleep hygiene and enhance performance.